Tracing the Jerusalem Code Volume 3: The Promised Land Christian Cultures in Modern Scandinavia (ca. 1750-ca. 1920) - Zorgati, Ragnhild Johnsrud; Bohlin, Anna (De Gruyter, 2021)
With the aim to write the history of Christianity in Scandinavia with Jerusalem as a lens, this book investigates the image - or rather the imagination - of Jerusalem in the religious, political, and artistic cultures of Scandinavia through most of the second millennium. Volume 3 analyses the impact of Jerusalem on Scandinavian Christianity from the middle of the 18. century in a broad context.